Ecoacoustics of small forest patches in agricultural landscapes: acoustic diversity and bird richness increase with patch size. Issue 1 (2nd January 2020) - Müller, Sandra; Shaw, Taylor; Güntert, Daniel; Helmbold, Lily; Schütz, Nina; Thomas, Luca; Scherer-Lorenzen, Michael
ABSTRACT: The species–area relationship is well documented across species in multiple ecosystems, and as such is widely accepted as one of ecology's key patterns. Although acoustic diversity has generally been correlated with species richness, the response of acoustic diversity to habitat size is unknown. Thus, we tested the transferability of the species–area relationship to a broader 'biodiversity–area relationship', investigating if acoustic diversity increases with habitat size. Twenty-two forest patches of increasing size (0.01–4.7 ha) in an agricultural area were inventoried for structural characteristics and bird richness. Plots were acoustically monitored over three time periods. Acoustic diversity values were related to habitat size, vegetation structural diversity and bird richness using linear regression analysis. We confirmed that acoustic diversity increased with forest patch size. When tested in separate models, bird richness and forest structural parameters explained variations in acoustic diversity equally well as forest patch size. Although the relative effects of patch size, bird richness and habitat heterogeneity are difficult to disentangle, acoustic diversity can be a useful proxy to study effects of forest fragmentation as it is subjected to a similar combination of drivers as traditionally surveyed metrics of biodiversity. Key policy insights: This study provides evidence that indices on acoustic diversity relate to vocalizing species diversity and forest structure, making these indices a useful tool to study biodiversity processes. This study confirms that decreasing habitat size correlates with decreasing biodiversity, for the first time including acoustic diversity as one aspect of biodiversity. This study underlines the importance of preserving forest patches in agricultural landscapes as refuges for biodiversity. Biodiversity can be enhanced by increasing forest patch size, reducing fragmentation and increasing habitat quality through enhancing structural diversity.